Pengaruh Virtual Learning Dengan Pembelajaran Jarak Jauh Terhadap Hasil Belajar Peserta Didik - Wati, Rina; Amelya, Gina Sonia; Setiawan, Agung; Wahyudi, Sri; Adyanata, Adyanata (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
This study aims to determine the effect of virtual learning with distance learning on student learning outcomes. The research method used in this study was Quasi Experiment by looking for the influence between X and Y. The population in this study were students of class XI TKJ SMK Negeri 2 Rambah, totaling 20 students with a sampling technique using total sampling where all populations became samples. Methods of data collection is done by using a test. Test the validity of the test instrument using the product moment relationship technique. The prerequisite analysis test consists of a normality test and a homogeneity test. The results of the study provide that virtual learning with distance learning has a significant effect on student learning outcomes.